The prophet - Gibran, Kahlil (First Avenue classics, 1923)
"Lebanese-American author Kahlil Gibran's The Prophet is one of the world's best-selling books of poetry. In twenty-six poetic essays, Gibran writes about marriage, death, and other topics. This unabridged edition was first published in 1923"--